Utilization of Number Line Media in Dienes' Step Learning: A Process Study to Overcome Difficulties in Integer Operations - Rohim, Abdur; Sa'Dijah, Cholis; Rahardi, Rustanto; Sisworo, Sisworo; Sukoriyanto, Sukoriyanto; Muksar, Makbul (SAINTIS Publishing, 2024)
Integers are an important topic in mathematics that students must understand well. However, in practice, many students face difficulties in understanding integer operations. One way to address this issue is by using a number line manipulative that employs Dienes' steps. This research is qualitative, with a case study approach. The subjects consisted of three 6th-grade students selected through purposive sampling. The three subjects had varying mathematical abilities: high, medium, and low. The learning activities used six steps of Dienes. The instruments used were observation sheets, interview guidelines, and a test consisting of eight questions related to the addition and subtraction of integers. Data collection techniques followed the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that learning using Dienes' steps with integer manipulatives successfully addressed students' difficulties in performing integer operations, especially in problems involving operations with two adjacent signs.